Effects of a Self-Efficacy Enhancing Program on Bowel Preparation Behavior and Bowel Cleanliness Quality in the Older Persons Undergoing Colonoscopy - Chaimongkol, Woraprat; Varitsakul, Rotsukon; Phengjard, Johnphajong (Nursing Research and Innovation Journal, 2025)
Older adults undergoing outpatient colonoscopy need to perform proper bowel preparation behaviors themselves to achieve adequate bowel cleanliness, ensuring safety during the procedure. Promoting bowel preparation behavior by increasing confidence in the practice should lead to correct behavior, resulting in good bowel cleanliness quality. This study aimed to investigate the effects of a self-efficacy enhancement program on bowel preparation behavior and bowel cleanliness quality. This quasi-experimental research included a sample of older adults undergoing colonoscopy at the special endoscopy unit of Nopparat Rajathanee Hospital. The inclusion criteria were: aged 60–79 years, medically indicated for colonoscopy, no previous colonoscopy experience, able to care of themselves, fully conscious and oriented as determined by a cognitive screening tool, able to communicate in Thai, and possession of a smartphone with internet access and the LINE application. Participants were divided into two groups: an experimental group and a control group, each comprising 35 participants. The control group received standard nursing care. The experimental group received the self-efficacy enhancement program during the pre-colonoscopy period, which consisted of four components: 1) physical and emotional readiness were assessed for fatigue, abdominal discomfort, and emotional state through inquiry and observation of facial expressions and body language. They were given time to rest and attend to their personal needs before participating in educational activities; 2) mastery experiences were provided with knowledge on bowel preparation through various media, including pamphlets, educational videos , and electronic documents sent via the LINE application. They also engaged in hands-on activities, such as planning meals that aligned with their daily routines; 3) vicarious experiences participants watched testimonial videos featuring older adults who had successfully completed bowel preparation; and 4) verbal persuasion motivational messages and reminders were delivered via the LINE official account on days 8, 7, 5, 2, and 1 prior to the scheduled colonoscopy. The research instruments included a personal information questionnaire, a bowel preparation behavior assessment form, which was validated by three experts with a content validity index (CVI) of 1 and a reliability coefficient (KR-20) of .714 and a bowel cleanliness record form, which is a standardized tool used to document the quality of bowel cleanliness as assessed by the colonoscopist and recorded in the patient’smedical records. Data collection was conducted from December 2023 to March 2024.The data were analyzed using descriptive statistics,including mean, percentage,and standard deviation,as well as inferential statistics, including the t-test and Mann–Whitney U test. The findings revealed that, followingthe intervention, the experimental group had a significantly higher mean rank score for overall bowel preparation behavior compared to the control group, with statistical significance at the.05 level.(U = 490,p<.05). Regarding the mean rank of bowel preparation behaviors in each aspect: the mean rank of the appropriate dietary intake aspect was not statistically significantly different (U = 542.50, p > .05) the mean rank of the laxativeuse aspect was statistically significantly different (U = 525,p<.05) and the mean rank of the medication use aspect affecting colonoscopy and proctoscopy was not statistically significantly different (U = 612.50,p> .05). However, the mean scores for bowel cleanliness quality in the left colon (t = -1.22,p> .05), transverse colon(t = -1.63,p> .05) , right colon(t = -.50,p> .05), and overall colon (t = -1.27, p > .05) showed no statistically significant differences between the groups. The findings of this study highlight the effectiveness of enhancing self-efficacy in promoting proper bowel preparation behavior. Therefore, nurses should support bowel preparation practices among older adults undergoing colonoscopy by providing close guidance and continuous motivational reminders. These efforts help strengthen confidence in performing bowel preparation correctly and effectively. Keywords: Bowel preparation behavior, Colonoscopy, Quality of bowel cleanliness,Self-efficacy